Carry over effect in pesticide residues analysis by LC - MS/ MS - MILIADIS, G.; MALATOU, P.; TSIANTAS, P.; VRETTAKOU, A.; EVANGELOU, V. I.; ANAGNOSTOPOULOS, Ch.; SIRAGAKIS, G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The Carry over effect, i.e. the appearance of a peak in the chromatogram of a blank analysis due to sample remaining from the previous analysis, was studied. The study was conducted for pesticide residues analysis by LC-MS/MS. In total 128 pesticides that belong to 13 different chemical classes were analyzed in order to investigate the cases that the effect is significant; i.e. a peak higher than 1% of the peak of the previous chromatogram appears. Carry over was found for 32 of the 128 studied pesticides (25%), at concentration levels between the LOD and 0.167 μg/mL. For 28 out of the 32 substances, more than two injections of a blank sample were required, as to reduce the effect significantly. Compounds presenting Carry over effect were mainly non-polar with logkow values between 4 and 7, characterized with very low water solubility, between 0.001 mg/L and 2 mg/L. On the contrary, the vapor pressure did not seem to be obviously related to the effect, as the substances presenting Carry over had various vapor pressure values, from 10-12 to 0.2 mP.